IPI reduction and reflexes in publics finances of Minas Gerais municipalities (Gestão & Regionalidade, 2021)
The IPI tax exemptions implemented by the Union to circumvent the negative effects of the global financial crisis significantly influenced the composition of the Municipal Participation Fund (FPM), the main source of financing of municipal public finances. Thus, this study aimed to verify whether the revenues of the municipalities of Minas Gerais and their socioeconomic indicators changed significantly after the federal government's IPI tax waiver from 2008. The results show that the small municipalities were the ones that suffered the most negative effects of the IPI reduction on the FPM. On the other hand, it was also found that for more than 50% of the municipalities analyzed there was an increase in the levels of tax collection and the amounts transferred under the FPM, due to the financial support granted by the Union.